2022
DOI: 10.3390/cancers14051135
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Urine Biomarkers to Improve Eligibility for Prostate Biopsy and Detect High-Grade Prostate Cancer

Abstract: PCa screening is based on the measurements of the serum prostate specific antigen (PSA) to select men with higher risks for tumors and, thus, eligible for prostate biopsy. However, PSA testing has a low specificity, leading to unnecessary biopsies in 50–75% of cases. Therefore, more specific screening opportunities are needed to reduce the number of biopsies performed on healthy men and patients with indolent tumors. Urine samples from 45 patients with elevated PSA were collected prior to prostate biopsy, a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“… 35 Another study reported that the expression of FCER2 was significantly decreased in prostate cancer, which could serve as a reliable biomarker to avoid unnecessary prostate biopsies and misdiagnosis. 36 In a nasopharyngeal carcinoma study, it was found that FCER2 was a downregulated gene in nasopharyngeal carcinoma, and its expression levels were significantly lower in nasopharyngeal carcinoma than in adjacent tissues. This gene was the first confirmed diagnostic marker related to immune cell infiltration in nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 35 Another study reported that the expression of FCER2 was significantly decreased in prostate cancer, which could serve as a reliable biomarker to avoid unnecessary prostate biopsies and misdiagnosis. 36 In a nasopharyngeal carcinoma study, it was found that FCER2 was a downregulated gene in nasopharyngeal carcinoma, and its expression levels were significantly lower in nasopharyngeal carcinoma than in adjacent tissues. This gene was the first confirmed diagnostic marker related to immune cell infiltration in nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, FCER2 was significantly associated with individual cancer stages, and the expression of FCER2 decreases with tumor progression 35 . Another study reported that the expression of FCER2 was significantly decreased in prostate cancer, which could serve as a reliable biomarker to avoid unnecessary prostate biopsies and misdiagnosis 36 . In a nasopharyngeal carcinoma study, it was found that FCER2 was a downregulated gene in nasopharyngeal carcinoma, and its expression levels were significantly lower in nasopharyngeal carcinoma than in adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the screening of csPCa becomes an important part of the treatment strategy (15). Studies have shown that approximately 75% of patients undergo unnecessary prostate biopsies based on PSA values only (16,17). Excessive biopsies lead to serious complications, such as urinary tract infections, pain, and hematuria (18).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the molecules mentioned above, according to the results of our literature search, HPX has rarely been reported in the context of cervical disease. However, its diagnostic value has been proven in gallbladder carcinoma, hepatocellular carcinoma, breast cancer, prostate cancer [ 39 41 ], and so on. Therefore, we believe that these five protein molecules (including SPARC) have the potential to be plasma biomarkers in cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%